Active Surveillance for Small Renal Masses - Pierorazio, Phillip M (MedReviews, LLC, 2012)
Small renal masses (SRMs; ≤ 4 cm in dimension) have rapidly risen in incidence in recent decades and pose an increasingly common management dilemma in urology. SRMs are biologically heterogeneous and a wide variety of treatments exist with favorable oncologic outcomes. Active surveillance (AS) has emerged as a viable option for those not desiring surgery or those who are suboptimal candidates for surgery, with < 2% of patients progressing to metastatic disease in retrospective and prospective studies. This article reviews the current data regarding AS for SRM, operational considerations for an AS program, and criteria for safely selecting patients for this treatment strategy.